A complicated tale of an acquired tracheoesophageal fistula: A case report - Vivek Manchanda; Mamta Sengar; Parveen Kumar (EL-Med-Pub, 2022)
Background: Esophageal atresia (EA) with distal trachea-esophageal fistula (TEF), the most common variety of EA, is managed by primary end-to-end anastomosis. Recurrent TEF constitutes the most difficult-to-manage complication of the primary repair and has an incidence of 2% to15%. Case Presentation: We present a case of rare recurrent TEF after primary repair of EA. The difficulties faced in view of the COVID pandemic and difficult diagnosis are discussed. We share our experience in the successful management of acquired TEF and lessons learned. Conclusion: Recurrent trachea-esophageal fistula is one of the rare and challenging complications to manage. The surgical option carries the best overall prognosis.